Exploration on pedestrian behaviour in Kuantan - Azharuddin, Anuar (2014)
Pedestrian behaviour study is important This because they are one of the most vulnerable road User compare to other road users. The aim of the research is to study the pedestrian behaviour based on the finding to improve the pedestrian safety. The behaviour of the pedestrian is studied and analysed trough interview on the pedestrian. And also trough observation on the pedestrian at the studied location. The relationship between variable (behaviour and background) is being analysed using contingency table and also associated statistical analysis. The majority of the pedestrian interviewed do not trust towards driver and also believe that drivers had careless attitude toward pedestrian. In the study site, there is still have pedestrian that no check the traffic before crossing. The study shows that either the pedestrian is a driver or non-driver brings effects towards their crossing behaviour. We also found that age above 45 (older pedestrian) had the higher percentage in crossing problems compare other group of age. Finally, some recommendation and suggestion are provided.